Снежная королева: сказка / художник Н. Фаттахова - Фаттахова Н. (Читаем по слогам, 2021)
Экземпляры: ДО мл.аб. (2021) / Инвентарный номер: 57313 / Цена: 17.50. / Сис.шифр: 82.3(0) / Авт.знак: С 53 / ГРНТИ: 17.82.93 / ББК: 82.3 (0)